THE TRADITION OF POETIC CREDENTIAL (????? ????) AND FARHANG AASFIA - Shamim Akhtar; Dr.Saima Shams (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Urdu lexicography is one of the treasures of literature through which one gets to know the meanings of words. Dictionary writing is also a literary necessity under which ancient and modern words are grasped. Where other dictionaries have blessed Urdu literature with vocabulary. Farhang Asafia’s status cannot be denied under any circumstances. This is the first complete dictionary of Urdu language and literature, which is the result of the hard work of a single person. According to Jaber Ali Syed, Farhang Asafia is a great and honorable linguistic achievement. It is not an easy task to find errors in it and to prove them correct. (1)